ANALYSIS OF INFLUENCE FACTORS THE REMAINING BUSINESS RESULTS IN VILLAGE UNIT COOPERATIVES IN KLATEN REGENCY - Muhammad Fajar Darojatun Pamungkas; Evi Gravitiani; Norlida Hanim Mohd Salleh (Journal of Applied Economics in Developing Countries, 2021)
The research that has been investigated aims to determine the effect of the number of members, own capital, external capital, and business volume on the remaining amount of cooperative business results. This research was conducted on 15 Village Unit Cooperatives in Klaten regency in 2013-2018. The data sources used in this study are secondary data and were taken from the Office of Trade, Cooperatives, and UKM, Village Unit Cooperatives, and the Central Statistics Agency which were then further processed. The data analysis method used is a multiple linear regression test. Research that has been conducted shows that the number of members, own capital, and business volume has a positive and significant effect on the remaining results of business. Still, on the other hand external capital has a negative and not significant effect on the remaining results of business. In addition, the number of members, own capital, external capital, and business volume simultaneously significantly affect.Keywords: Remaining Operating Results; Own Capital; External Capital; Business Volume; Village Unit Cooperatives